THE GROWTH OF Dendrobium spectabile (Blume) Miq. ORCHID PLANTLET IN VACIN AND WENT (VW) MEDIUM WITH DIFFERENT CONCENTRATIONS OF COCONUT WATER - Zakiyah, Aisyah; Setiari, Nintya; Nurchayati, Yulita (BRIN Publishing (Penerbit BRIN), 2025)
Dendrobium spectabile is an epiphytic orchid that grows slowly and experiences natural exploitation, so it needs to be conserved ex-situ through in vitro culture. One of the essential steps for in vitro culture is subculture to supply the nutrients needed by plantlets. Increasing the growth of these plantlets can be done by adding coconut water. This study aimed to determine the effect of adding coconut water and the optimal concentration of coconut water on the growth of D. spectabile plantlets in VW medium. The method used is growing plantlets in VW medium with different concentrations of coconut water. The research design was completely randomized with a single factor, the concentration of coconut water (0%, 5%, 10%, 15%, 20%). Data were analyzed by ANOVA at a 5% significance level. Plantlet growth was observed for two months. Parameters observed were new shoots, leaves, and roots emergence time; number of new shoots, leaves, and roots; and new leaves length. The addition of coconut water affected the growth of D. spectabile orchid plantlets. Five to ten percent of coconut water is the optimal concentration for shoots and leaves growth of D. spectabile orchid plantlets. Therefore, coconut water can increase the growth of in vitro plantlets.